KAJIAN PERAN BAHAN PEMUTIH NATRIUM PIROPOSPHATE (Na2H2P2O7) TERHADAP PROSES PEMBUATAN TEPUNG UBI JALAR (Jurnal Teknologi Pangan, 2013)
The  study  aims  to  determine  the  effect  of  bleaching  on  sweet  potato  flour.  The specified condition  is  weight  300  g  sweet  potato,  with  white  colour and Piroposphate Sodium  (Na2H2P2O7) concentration:  0;    0.3;  0.6;   0.9;  1.2  g  And  soaking  time:  5;  10; 15; 20; 25 minutes. The results obtained  the best degrees of color at concentration of 1.2 g with 25-minute immersion time of 30 TCU, the lowest obtained at concentrations of  0  g  0  minutes  by  long  immersion  in  the  amount  of  5.0  TCU.  To  obtain  the  best conditions  of  water  content  at  a  concentration  of  1.2  grams  with  a  long  soaking  25 minutes  in  the  amount  of  11.78%,  the  lowest  obtained  at  concentrations  of  0  g  0 minutes by long immersion in the amount of 7.8%. For  the largest starch content was obtained  at  a  concentration  of  0.6  g  with  25-minute  long  immersion  in  the amount  of 28.54%, the lowest obtained at concentrations of 0 g to 25 minutes long immersion in the amount of 26.66%.Keywords: Sodium Piroposphate, flour, sweet potatoes, bulbs, bleach